Behavioral therapy in diabetes mellitus and obesity - Istvan Sal; Ildiko Kohlne (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2018)
In Weimar, on the wall of Albert Schweitzer Museum, there is a memorial tablet which says: "The purpose of our life is to serve, to show solidarity and helpfulness." The humanist medical doctor, theologian, philosopher, organist could not have expressed more clearly our confession. Behavioral therapy integrates the cure of body and soul, which occasionally show some duality and opposition.